Globalization and the environment - Vally Koubi; Thomas Bernauer (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
We study the effects of economic globalization (liberalization of international trade and investment flows) on the environment in the context of a model that integrates standard factor endowment theory (FET) with the pollution haven hypothesis (PHH). Both FET and PHH imply that inward investment burdens the environment while outward investment is favorable for environmental quality. The model suggests that FET and PHH can be discriminated on the basis of the effects of the interaction between trade in goods and inward FDI on the environment. In particular, the interaction is positive under the former and negative under the latter theory. We examine the effects of FDI for SO2 concentrations in a large set of countries during the last two decades. We find that inward FDI is associated with higher concentrations while outward FDI is associated with lower concentrations. And that increased FDI amplifies the effects of increased trade. The last result constitutes prima facie evidence in favor of the PHH over the FET.
Keywords: 330; FDI; trade; environment; pollution haven; factor endowments; SO2